(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
The Internet of Things (IoT) introduces new security considerations because connected devices typically have limited computational resources, making traditional cryptographic algorithms inefficient. RSA, a widely used public-key cryptosystem, is particularly resource-intensive due to its large key sizes and heavy arithmetic operations. This study investigates the inefficiency of standard RSA in resource-constrained IoT environments and evaluates optimization strategies aimed at improving performance without compromising security. Enhancements include key size reduction, the use of the Chinese Remainder Theorem (CRT) for decryption, and precomputation techniques. Performance was assessed in a simulated IoT environment, measuring execution time, memory consumption, and energy efficiency. Security considerations, including potential vulnerabilities of CRT-based RSA such as differential fault attacks, were addressed through redundancy and verification mechanisms. Comparative insights with Elliptic Curve Cryptography (ECC) and post-quantum lightweight schemes (e.g., Ascon, Kyber-SLH-DSA) were provided to contextualize the results. The findings show that optimized RSA achieves significant reductions in computational overhead and energy consumption while maintaining correctness, demonstrating its feasibility for low-power IoT devices. Hybrid cryptography approaches, combining RSA key exchange with symmetric AES payload encryption, are recommended for future implementations. These results reinforce that efficient and practical public-key encryption is achievable in constrained IoT systems while preserving strong security.